1992
DOI: 10.3720/japt.57.91
|View full text |Cite
|
Sign up to set email alerts
|

Basalts of Nishikurosawa Stage of Early to Middle Miocene in the Akita and the Niigata Oil Fields, Northeast Japan.

Abstract: Thick basaltic piles of Nishikurosawa stage of early to middle Miocene age are widely distributed from Akita through Yamagata to Niigata oil fields along the Japan Sea side. Recently, MITI Nikaho Well and MITI Niigata-heiya Well were drilled at the foot of Mt. Chohkai in the southern part of Akita, and at the central part of the Niigata plain, respectively. Both wells encountered a thick basaltic layer ranging up to 1,400 meters of the Nishikurosawa stage. We studied micropaleontological features and petrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Radiometric age in red: this study. (1) Sato and Sato (1992), (2) Sato et al (1991), (3) Ozawa et al (1982), (4) Ozawa and Ohguchi (1979), (5) Ozawa et al (1988), (6) Aida (1984), (7) Kato and Yanagisawa (2021), (8) Usuta et al (1978), (9) Tsuji et al (1991), (10) Kato et al (2008), (11) Yoshioka et al (2021).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Radiometric age in red: this study. (1) Sato and Sato (1992), (2) Sato et al (1991), (3) Ozawa et al (1982), (4) Ozawa and Ohguchi (1979), (5) Ozawa et al (1988), (6) Aida (1984), (7) Kato and Yanagisawa (2021), (8) Usuta et al (1978), (9) Tsuji et al (1991), (10) Kato et al (2008), (11) Yoshioka et al (2021).…”
Section: Geologic Settingmentioning
confidence: 99%
“…O. Sato and Sato (1992) reported that the calcareous nannofossil assemblages in mudstones amongst the lower part of the basaltic rocks and in mudstones that overlie the basaltic rocks are from Ma) biozones of Martini (1971), respectively. A benthic foraminifera assemblage in the Tachiyazawa Formation, which is overlain by the Aosawa Formation to the south of the study area, has been correlated with the N8 (16.38-15.10 Ma) planktonic foraminiferal biozone (H. Sato et al, 1986).…”
Section: Geological Settingmentioning
confidence: 99%
“…In the center of the Akita Basin as well as of the Niigata Basin, thick piles of basalts accumulated in grabens [34][35]. The Middle Miocene northeast Japan was characterized by a distinct bimodal volcanism in which basalts dominated in back-arc side whereas fore-arc side was dominated by felsic rocks [23].…”
Section: Rapid Riftingmentioning
confidence: 99%